The Potential of Halal Tourism Industry in Uzbekistan - Aniqoh, Nur Aini Fitriya Ardiani; Hanik, Umi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Halal Tourism is one indicator of success in bringing in foreign exchange, especially in the tourism sector. In addition, halal tourism can provide security and comfort for Muslim tourists visiting the country. This study aims to find out the potential of the halal tourism industry in Uzbekistan, a country located in Central Asia, while developing halal tourism. The method in this study uses a qualitative approach using secondary data sources. This study shows that Uzbekistan has managed to rank 16 according to the Global Muslim Travel Index in 2021, up 4 places from the previous year. This is something good for the development of halal tourism in Uzbekistan. So that Uzbekistan can maintain the advantages of halal tourism with unique historical tourist attractions, visa exemptions, and delicious culinary tours. So, Uzbekistan can also improve its shortcomings in the communication sector and access connectivity and transportation infrastructure.